Hypoglycemic and hypolipidemic effects of Oligomeris linifolia in Alloxan-induced diabetic mice - Ashiq, Aisha; Jan, Saleem; Khan, Yar Muhammad; Ullah, Faizan; Balaraman, Ashok Kumar; Azad, Abul Kalam; Khan, Tanveer Ahmad; Helal Uddin, A.B.M. (Association of Biotechnology and Pharmacy, 2023)
The current study was focused to evaluate the hypoglycemic and hypolipidemic effect of methanolic extracts of Oligomeris linifolia in Alloxan-induced diabetic mice. Albino mice were orally treated for 15 days with methanolic extract of Oligomeris linifolia at dose of 200 mg/kg body-weight. The antidiabetic effect was analyzed by measuring blood glucose (BG) at 0, 3, 6, 9, 12, and 15 days. Total cholesterol (TC), high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C), Serum Bilirubin (SBR), Alkaline Phosphatase (ALP), Alanine Aminotransferase (ALT), Urea, Creatinine, and triglycerides (TG) levels at sacrifice (day 16) were measured. Glibenclamide (10 mg/kg) was used as standard. Alloxan-induced diabetic mice showed adequate to significant increase in the level of BG, TC, TG, LDL-C, SBR, ALT, ALP, Urea, Creatinine, while HDL-C and body-weight were decreased as compared to control group (non-diabetic mice). Administration of plant methanolic extract to Alloxan-induced dabetic mice at a dose of 200 mg/kg body-weight resulted in a notable decrease in BG, TC, TG, LDL-C, SBR, ALT, ALP, Urea and Creatinine whereas HDL-C level and body-weight were increased markedly after 15 days as compared to diabetic control group. The methanolic extract at the dose of 200 mg/kg, produced similar results compared to group treated with Glibenclamide.